"Mother-weights" and lost fathers: parents in South Asian American literature - Maxey, Ruth (Routledge, 2012)
That parent-child relationships should play a significant role within South Asian American literature is perhaps no surprise, since this is crucial material for any writer. But the particular forms they so often take – a dysfunctional mother-daughter dynamic, leading to the search for maternal surrogates; and the figure of the prematurely deceased father – are more perplexing. Why do families adhere to these patterns in so many South Asian American texts and what does that tell us about this œuvre? More precisely, why are mothers subjected to a harsher critique than fathers and what purpose does this critique serve? How might we interpret the trope of the untimely paternal death? In this article I will seek to answer these questions – arguably key to an understanding of this growing body of writing – by considering works produced between the 1990s and the early twenty-first century by a range of South Asian American writers.